2018
DOI: 10.1177/0894318418774884
|View full text |Cite
|
Sign up to set email alerts
|

Attaining Mutual Goals in Telehealth Encounters: Utilizing King’s Framework for Telenursing Practice

Abstract: Access to essential health-promoting nursing care is increasingly facilitated through the expanding scope and capabilities provided through the utilization of telehealth technologies. Telehealth technologies facilitate the nursing process with clients at a distance in multiple ways, such as video conferencing, video conferencing with peripheral diagnostic tools, and store and forward modalities. Nursing care needs to remain the focus of care, but technology is a useful ancillary tool to help clients achieve he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…WeChat and E-mail are daily communication tools for the public and their beneficial value in health education has been clinically confirmed [13] . Fronczek research also shows that King's interactive compliance theory is helpful to improve the effect of distance education [14] . This study provided an online communication platform for communication among patients and communication between nurses and patients by establishing WeChat group, thus shortening the distance between patients and nurses and helping nurses to play a coordinating role to ensure more effective clinical nursing.…”
Section: Resultsmentioning
confidence: 98%
“…WeChat and E-mail are daily communication tools for the public and their beneficial value in health education has been clinically confirmed [13] . Fronczek research also shows that King's interactive compliance theory is helpful to improve the effect of distance education [14] . This study provided an online communication platform for communication among patients and communication between nurses and patients by establishing WeChat group, thus shortening the distance between patients and nurses and helping nurses to play a coordinating role to ensure more effective clinical nursing.…”
Section: Resultsmentioning
confidence: 98%
“…Many studies have outlined that patient satisfaction improves communication (35). Similarly, findings in one tele health research (36) showed the importance of communication in mutual goal setting. Communication was shown to be an important aspect in successful patient therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Further inquiry and research is needed as to how virtual care provided by nurses can assist clients in attaining health-related goals in a safe and effective manner. Nurses could also study King’s concepts of authority, power, and decision-making that may be reconceptualized for a virtual care environment that is now becoming an emerging part of King’s interpersonal and social systems (Fronczek & Rouhana, 2018). For example, nurses will need to know what the perceptions of the virtual care spaces are for individuals and how they may or may not be realistic perceptions.…”
Section: Nursing Theoretical Considerations For Virtual Carementioning
confidence: 99%